A Permian large igneous province in Tarim and Central Asian orogenic belt, NW China: Results of a ca. 275 Ma mantle plume? - Zhang, C.; Li, Zheng-Xiang; Li, X.; Xu, Y.; Zhou, G.; Ye, H. (Geological Society of America, 2010)
New sensitive high-resolution ion microprobe (SHRIMP) U-Pb zircon ages, geochemical data, and a synthesis of existing stratigraphic, geochronologic, and geochemical results from the Tarim block and the Central Asian orogenic belt in northwestern China suggest the presence of a Permian (ca. 275 Ma) large igneous province (the Bachu large igneous province). The large igneous province consists predominantly of coeval mafic rocks (basalts and mafic-ultramafic intrusions) having an aerial coverage of more than 600,000 km2, and its formation was accompanied by voluminous emplacement of A-type granites. This large igneous province, interpreted to be of mantle plume origin, is ~15 m.y. older than the ca. 260 Ma Emeishan large igneous province in southwestern China and ~25 m.y. older than the 251 Ma Siberian Trap in Russia.Such a sudden flair up of plume activity in the Permian may representthe early stage of the Pangean superplume event. The Permian plumes likely played a role in late Paleozoic rapid continental crustal growth in the Central Asian orogenic belt. In addition, there appear to be two types of mantle geochemical provinces (domains) in the region, a long-term enriched Tarim province and a subduction-metasomatized and depleted Central Asian orogenic belt province.